Pengaruh Media Sosial TikTok dan Motivasi Belajar terhadap Hasil Belajar Siswa Kelas V di Gugus IV Sandubaya - Ramadhan Abdul Jalil; Ida Ermiana; Nurkhaerat Alimuddin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to empirically examine the influence of TikTok social media usage and learning motivation on students’ learning outcomes. This explanatory survey research involved 131 fifth-grade students from Cluster IV Sandubaya as research participants. Data were collected through questionnaires and documentation techniques, then analyzed using simple linear regression and Moderated Regression Analysis (MRA). The findings revealed that the use of TikTok social media did not have a significant influence on students’ learning outcomes, as indicated by the significance value obtained (p = 0.295 > 0.05). In contrast, learning motivation showed a significant influence on students’ learning outcomes (p = 0.001 < 0.05), indicating that students with higher learning motivation tended to achieve better academic performance. Furthermore, the interaction test results demonstrated that learning motivation was unable to moderate the influence of TikTok social media usage on students’ learning outcomes (p = 0.199 > 0.05). These findings suggest that the level of learning motivation does not strengthen or weaken the relationship between TikTok usage and learning outcomes among fifth-grade students in Cluster IV Sandubaya. Therefore, learning motivation remains an important factor in improving students’ academic achievement.